How Experience, Attention And Ubiquity Economies Affect The Role Of Digital Media Art And Artists - da Veiga, Pedro Alves; Tavares, Mirian; Alvelos, Heitor (Journal of Tourism, Sustainability and Well-being, 2017)
This article seeks to demonstrate the impact three economic concepts that gained traction in the last decades of neoliberalism – experience, attention and ubiquity – have caused in the current role of digital arts and artists in society, both on and off-line, as well as how they have changed the arts ecosystem, namely by altering the relationships between artists, audience, curating, public spaces – material and virtual, academia and companies. It addresses the commoditisation of creativity and innovation, which are now organised and consumed like products. It also offers insights on how the concept of art ownership has been replaced by experience, how mass-individualization of the selfie generation artists in a globally aestheticised and exposure-addicted world has contributed to the dismantling of community and association mind-sets and how the architecture of participation, presented as a vector of globalisation, inclusion, and democratisation of access to creation and enjoyment, actually revealed itself as a vector of inequality. It concludes by showing how hacktivism and artivism rise as new vanguards in an environment that is written and reads itself, bridging materiality and virtuality, in a multiplicity of blended spaces.